MiR‐145‐targeted HBXIP modulates human breast cancer cell proliferation - Jiang, Yang (Thorac Cancer, 2018)
BACKGROUND: MiR‐145 has been identified as a tumor suppressive microRNA in multiple cancers. In this current investigation, we searched for new direct targets of miR‐145 and evaluated their effect on breast cancer development. METHODS: Targetscan was used to predict the target genes of miR‐145. The targeting of miR‐145 on oncogenic HBXIP was verified by luciferase reporter gene analysis. The effect of miR‐145 on the level of messenger RNA and protein of HBXIP was evaluated by quantitative real‐time PCR and immunoblotting. Correlations between miR‐145 and HBXIP, as well as miR‐145 expression, were analyzed in 30 paired breast cancer and noncancerous tissues by quantitative real‐time PCR. Methyl thiazol tetrazolium and colony formation assays were applied to determine the cell proliferation ability. RESULTS: HBXIP was identified as a novel target gene of miR‐145 in breast cancer. MiR‐145 was found to dose‐dependently decrease messenger RNA and protein expression of HBXIP in breast cancer MCF‐7 cells. Notably, miR‐145 expression was negatively related to HBXIP expression and was obviously reduced in breast cancer samples. Finally, miR‐145 suppressed cell proliferation while its inhibitor, anti‐miR‐145, accelerated cell proliferation. Interestingly, silencing of HBXIP reversed the acceleration of cell proliferation induced by anti‐miR‐145 in breast cancer. CONCLUSION: Oncogenic HBXIP is a new direct target of tumor suppressive miR‐145. Our findings reveal that miR‐145‐targeting HBXIP could be a potential therapeutic target in breast cancer.